Adenosine Receptor Heteromers and their Integrative Role in Striatal Function. (2007) - Ferré, Sergi; Ciruela, Francisco; Quiroz, César; Luján, Rafael; Popoli, Patrizia; Cunha, Rodrigo A.; Agnati, Luigi F.; Fuxe, Kjell; Woods, Amina S.; Lluis, Carme; Franco, Rafael
Abstract : By analyzing the functional role of adenosine receptor heteromers, we review a series of new concepts that should modify our classical views of neurotransmission in the central nervous system (CNS). Neurotransmitter receptors cannot be considered as single functional units anymore. Heteromerization of neurotransmitter receptors confers functional entities that possess different biochemical characteristics with respect to the individual components of the heteromer. Some of these characteristics can be used as a "biochemical fingerprint" to identify neurotransmitter receptor heteromers in the CNS. This is exemplified by changes in binding characteristics that are dependent on coactivation of the receptor units of different adenosine receptor heteromers. Neurotransmitter receptor heteromers can act as "processors" of computations that modulate cell signaling, sometimes critically involved in the control of pre- and postsynaptic neurotransmission. For instance, the adenosine A1 -A2A receptor heteromer acts as a concentration-dependent switch that controls striatal glutamatergic neurotransmission. Neurotransmitter receptor heteromers play a particularly important integrative role in the "local module" (the minimal portion of one or more neurons and/or one or more glial cells that operates as an independent integrative unit), where they act as processors mediating computations that convey information from diverse volume-transmitted signals. For instance, the adenosine A2A -dopamine D2 receptor heteromers work as integrators of two different neurotransmitters in the striatal spine module.